Halide‐directed Assembly of Mercury(II) Coordination Polymers for Electrochemical Biosensing Toward Penicillin. Issue 5 (25th February 2020) - Xue, Ya‐Qi; Bi, Yan; Chen, Jing
Abstract : Three 1D/2D Hg II coordination polymers (CPs), namely {[Hg3 (L)2 Cl6 ](H2 O)} n (1 ), [Hg(L)Br2 ] n (2 ), and [Hg(L)I2 ] n (3 ) were prepared by assembly of 3, 4‐bis(3‐pyridyl)‐5‐(4‐pyridyl)‐1, 2, 4‐triazole (L) with different inorganic Hg II salts (i.e. HgCl2, HgBr2 or HgI2 ). Single‐crystal X‐ray diffraction analysis reveals two types of bimetallic subunits [(Hg)2 C6 N4 ] and [(Hg)2 C12 N6 ] in CP 1, which are further extended to a 2D coordination network. Both of CPs 2 and 3 show 1D zigzag arrays bridged by L ligands. Notably, the L ligands take the (η 4, μ4 ) coordination fashion in 1 but (η 2, μ2 ) binding mode in 2 and 3 . The structural differences of CPs 1 –3 indicate that the L ligand can adjust its coordination fashions to meet the requirements of Hg II centers, relying on the presence of distinct halide anions. In addition, 1 can be applied to fabricate an electrochemical biosensor for the detection of penicillin. Abstract :